A Cross – Sectional Study: The Correlation Between Premenstrual Syndrome and Quality of Life Among Midwifery Students at Universitas Pendidikan Ganesha - Putu Cynthia Devi Irmayanti; Luh Yenny Armayanti; Lia Puspitasari (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
Premenstrual syndrome (PMS) is a common condition among women of reproductive age, characterized by recurrent physical, emotional and behavioral symptoms during the luteal phase of the menstrual cycle. These symptoms may negatively affect academic performance and quality of life (QoL), particularly among midwifery students. This study aimed to examine the correlation between PMS severity and quality of life among midwifery students. A cross – sectional study was conducted among midwifery students using the Premenstrual Syndrome Scale (PMSS) and the WHOQOL – BREF questionnaire. PMS severity and QoL domains – physical health, psychological health, social relationship and environment – were analyzed using Pearson correlation with significance level of p < 0,05. The findings showed that 9,52% of participants had poor QoL, 60,71% had moderate QoL and 29,76% had good QoL. PMS severity was significantly and negatively correlated with all QoL domains ( p = 0,001). The strongest correlation was observed in the physical domain ( r = -0,605), followed by psychological health (r = -0,574), social relationship ( r = -0,459) and environment ( r = -0,405). These results indicate that higher PMS severity is associated with lower QoL scores among midwifery students. PMS significantly affects the quality of life of midwifery students, especially in physical and psychological aspects. Early management and supportive interventions are essential to improve students well – being and academic performance.